Pelatihan Pengelolaan Keuangan dan Pemasaran untuk UMKM di Desa Kertomulyo Kecamatan Trangkil Kabupaten Pati - Miladia Fadilasari; Amalia Dewi Ikawati; Sinta Yulia Permatasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
MSMEs play an important role in the village economy, but many business actors still face obstacles in managing finances and marketing their products effectively. This community service aims to improve the understanding and skills of MSME actors in Kertomulyo Village, Trangkil District, Pati Regency in terms of financial management and marketing strategies. This training is carried out through an easy-to-understand approach, including simple financial recording, business capital management, and digital marketing strategies using social media. Participants are trained to record income and expenses systematically so that they can better understand the financial condition of their business. In addition, they are also taught how to promote products online in order to reach a wider market. The results of this activity show an increase in the participants' understanding and skills in managing finances and implementing more effective marketing techniques. With this training, it is hoped that MSMEs in Kertomulyo Village can develop more rapidly, increase competitiveness, and expand their marketing networks.